2010
DOI: 10.1002/cncy.20060
|View full text |Cite
|
Sign up to set email alerts
|

Does the time of day or weekday affect screening accuracy?

Abstract: BACKGROUND: Workload is extensively regulated in gynecologic cytology. However, sensitive monitors of excessive workload are not available. METHODS: We measured the variation in abnormal (atypical squamous cells [ASC], lowgrade squamous intraepithelial lesion [LSIL], and high-grade squamous intraepithelial lesion [HSIL]) rates for 4 cytotechnologists (CTs) among different days of the week and at different times during the day while they were performing primary screening with the ThinPrep Imaging System. RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 15 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Extensive studies have explored the adverse outcome of later time of day on clinical performance in other domains, such as increasing omission errors and false positives among radiologists and decreasing abnormal cytology detection rates on gynecologic cytology samples among cytotechnologists. 18,19 Radiologists reported eyestrain and blurred vision with an increased number of images read. They hold an opinion that time day significantly impacts reading competence-related cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have explored the adverse outcome of later time of day on clinical performance in other domains, such as increasing omission errors and false positives among radiologists and decreasing abnormal cytology detection rates on gynecologic cytology samples among cytotechnologists. 18,19 Radiologists reported eyestrain and blurred vision with an increased number of images read. They hold an opinion that time day significantly impacts reading competence-related cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Although a majority of the literature illuminating the effects of cytotechnologist fatigue on the processing of cytopathology specimens is in the setting of cervical smear samples, the processing of FNA samples is similar and may hold true. [ 14 15 ] Some studies have reported cytology failure rates of as high as 31% due to cytotechnologist fatigue. [ 18 ] It is difficult to separate the endoscopist's fatigue from cytological technician's failure since the two are so intertwined in EUS-FNA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Recent reports have indicated that the time of day and the workload of the cytotechnologist impact the detection rate of abnormal cytology on gynecologic cytology samples, with more abnormal results being detected from morning samples as compared to evening samples and from samples taken later in the week when compared to those obtained earlier in the week. [ 14 15 ] Operator fatigue has not been previously examined in relation to the diagnostic accuracy of EUS-FNA. The objective in this study was to explore our institution's experience with EUS-FNA of solid pancreatic masses to elucidate if the procedure time or queue position has an impact on the overall performance characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The screening time for each slide (including any reviews by the supervisor) and the maximum workloads per cytologist considered in our study, based on those in the international literature [31,32,33,34,35,36,37,38], are shown in table 1. Fully automatic computer-assisted screening reduced the time of conventional cytology by 64% and of LBC by 40%.…”
Section: Resultsmentioning
confidence: 99%